2010
DOI: 10.1118/1.3301574
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculated absorbed‐dose energy dependence of EBT and EBT2 film

Abstract: Purpose:The absorbed-dose energy dependence of GAFCHROMIC EBT and EBT2 film irradiated in photon beams is studied to understand the shape of the curves and the physics behind them. Methods: The absorbed-dose energy dependence is calculated using the EGSnrc-based EGS_cham-ber and DOSRZnrc codes by calculating the ratio of dose to water to dose to active film layers at photon energies ranging from 3 keV to 18 MeV. These data are compared to the mass energy absorption coefficient ratios and the restricted stoppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
131
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 12 publications
6
131
1
3
Order By: Relevance
“…However, energy dependence and dose dependence of EBT films become more significant when both beam energy and dose quantity are lower 21 , 22 . This can explain the increasing discrepancies between the film and the two other dosimeters with off‐axis distances, as well as with depth.…”
Section: Discussionmentioning
confidence: 99%
“…However, energy dependence and dose dependence of EBT films become more significant when both beam energy and dose quantity are lower 21 , 22 . This can explain the increasing discrepancies between the film and the two other dosimeters with off‐axis distances, as well as with depth.…”
Section: Discussionmentioning
confidence: 99%
“…For MV beams, EBT, EBT2, and EBT3 GAFCHROMIC film models were used extensively to measure therapeutic doses over wide dose range and the same dosimetry protocols apply for imaging. The dosimetric properties of these films were tested widely in the literature in terms of absorption spectra, (24) postirradiation waiting time, 24 , 25 scanning mode and exposure to light, 25 , 26 high temperature behavior, (25) performance in water, (27) depth dose measurements, (28) and energy dependence 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…The calibration curve takes various forms depending on the type of radiochromic films [7,8]. The calibration curve of GAFCHROMIC EBT2 (GAF-EBT2: International Specialty Products, Wayne, NJ) shows minimal curvature in the recommended dose range by manufacture [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, measurement of the second half-value layer was impossible due to the energy-dependent influence in the highenergy range. On the other hand, GAF-EBT2 has been shown to be capable of measuring the second HVL, because it shows only slight energy dependency errors in comparison with GAF-R and other radiochromic films [8,[11][12][13][14][15]. For these reasons, in HVL measurements of devices operating in the high-energy range (X-ray CT, radiotherapy machines, and so on), it is suggested that GAF-EBT2 offers higher measurement precision than GAF-R.…”
Section: Introductionmentioning
confidence: 99%